3D printed titanium implants: colossal FDA-approved leap towards “personalized” maxillo-facial surgery. - Aidar, Ziyad (Journal of Oral Research, 2019)
Global health initiatives, over the last years, have often struggled to implement impactful vicissitudes, whether in preventive or interventional, and more so, surgical care1. This can be mainly attributed to (a) deficiencies in comprehending what aspects govern the capacity of a surgical service to deliver safe, efficacious, accessible, and cost-effective care; and (b) whether the surgical service/care meets the mounting needs and demands of populations.